Utveckling av datamodell för kompetenskartläggning - Gunnarsson, David (2015)
Nowadays there are many service providers on the market, among them consulting firms whose mission is to sell knowledge. This knowledge is held by employees in these firms in the form of competences. In order to match competences and customer orders information systems can be used, although some companies prefer to keep track of the competences manually. The type of information system used for this purpose is the Human Resource Management System (HRMS). However, only a certain part of the HRMS is used for compe-tence matching. The HRMS is part of the bigger Enterprise Resource Planning system (ERP).The purpose of this report was to find a way for service providers to store employees’ com-petences in a database in a way that provides relevant search results when searching for competences in the company’s system. I have been in contact with an international IT con-sulting firm in Luleå where I also tested by solution. A preliminary study was conducted that resulted in a list of demands from the company, as well as other companies’ approach to the problem situation. A database model was developed, as well as search terms to validate the database model. The search terms gave the search results that were expected and I there-fore believe that the database model is now complete, although there is room for further development. Validerat; 20150825 (global_studentproject_submitter)